Me ajudem, estou com dúvida nessa questão
Anexos:
![](https://pt-static.z-dn.net/files/dd3/2e9d61376c0903c68b5bfa2709a2c772.jpg)
Soluções para a tarefa
Respondido por
1
a)+10ab^2
b)(-4m^4n)
resolvendo:
a)+10ab^2+8ab^2-3ab^2=+15ab^2
+18ab^2-3ab^2=+15ab^2
+15ab^2=+15ab^2
b)9m^4n-(-4m^4n)+15m^4n=+28m^4n
9m^4n+4m^4n+15m^4n=+28m^4n
13m^4n+15m^4n=+28m^4n
+28m^4n=+28m^4n
b)(-4m^4n)
resolvendo:
a)+10ab^2+8ab^2-3ab^2=+15ab^2
+18ab^2-3ab^2=+15ab^2
+15ab^2=+15ab^2
b)9m^4n-(-4m^4n)+15m^4n=+28m^4n
9m^4n+4m^4n+15m^4n=+28m^4n
13m^4n+15m^4n=+28m^4n
+28m^4n=+28m^4n
Perguntas interessantes
História,
11 meses atrás
Filosofia,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Saúde,
1 ano atrás